Biallelic variants in ERLIN1: a series of 13 individuals with spastic paraparesis - Cogan, Guillaume; Zaki, Maha S.; Issa, Mahmoud; Keren, Boris; Guillaud-Bataille, Marine; Renaldo, Florence; Isapof, Arnaud; Lallemant, Pauline; Stevanin, Giovanni; Guillot-Noel, Lena; Courtin, Thomas; Buratti, Julien; et al. (Human genetics, 2024)
Biallelic variants in the ERLIN1 gene were recently reported as the cause of two motor neuron degeneration diseases, SPG62 and a recessive form of amyotrophic lateral sclerosis. However, only 12 individuals from five pedigrees have been identified so far. Thus, the description of the disease remains limited. Following the discovery of a homozygous pathogenic variant in a girl with SPG62, presenting with intellectual disability, and epilepsy, we gathered the largest series of SPG62 cases reported so far (13 individuals) to better understand the phenotype associated with ERLIN1 . We collected molecular and clinical data for 13 individuals from six families with ERLIN1 biallelic variants. We performed RNA-seq analyses to characterize intronic variants and used Alphafold and a transcripts database to characterize the molecular consequences of the variants. We identified three new variants suspected to alter the bell-shaped ring formed by the ERLIN1/ERLIN2 complex. Affected individuals had childhood-onset paraparesis with slow progression. Six individuals presented with gait ataxia and three had superficial sensory loss. Aside from our proband, none had intellectual disability or epilepsy. Biallelic pathogenic ERLIN1 variants induce a rare, predominantly pure, spastic paraparesis, with possible cerebellar and peripheral nerve involvement.